1998
DOI: 10.1017/s0020860400091555
|View full text |Cite
|
Sign up to set email alerts
|

The new International Criminal Court: A preliminary assessment

Abstract: After years of relentless effort and five weeks of intense and difficult negotiations, the Statute of the International Criminal Court (ICC) was adopted and opened for signature in Rome on 17 July 1998. This historic event represents a major step forward in the battle against impunity and towards better respect for international humanitarian law. For too long it has been possible to commit atrocities with total impunity, a situation which has given perpetrators carte blanche to continue such practices. The sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Advocates have suggested that the legal age for recruitment should be set at 18 years of age and 21 years for active combat. 51 As of 1 November 2006, there were 122 signatories and 122 parties to the Protocol including three of the five permanent members of the Security Council: France; the UK; and the US. 52 However, the Russian Federation and the Peoples Republic of China remain non-parties.…”
Section: The Un Commission On Human Rights Working Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…Advocates have suggested that the legal age for recruitment should be set at 18 years of age and 21 years for active combat. 51 As of 1 November 2006, there were 122 signatories and 122 parties to the Protocol including three of the five permanent members of the Security Council: France; the UK; and the US. 52 However, the Russian Federation and the Peoples Republic of China remain non-parties.…”
Section: The Un Commission On Human Rights Working Groupmentioning
confidence: 99%
“…Advocates have suggested that the legal age for recruitment should be set at 18 years of age and 21 years for active combat. 57 As of 1 June 2008, 108 countries are states parties to the Rome Statute of the International Criminal Court. However, the United States, the Russian Federation and the Peoples Republic of China remain non-parties.…”
Section: The Un Commission On Human Rights Working Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…The ICRC welcomed the text of the ICC Statute as a major step forward in the battle against impunity. 27 Representatives of the ICRC took an active part in the negotiations which led to adoption of the Statute and subsequently of the Elements of Crime on issues directly relating to the ICRC's mandate as the promoter and guardian of international humanitarian law. 28 Nevertheless, at a time when the positive outcome of the ICTY case was not yet known, there was much discussion within the ICRC on how best to protect the confidentiality of its information in situations involving the ICC.…”
Section: The Rules Of Procedures and Evidence Of The Icc 26mentioning
confidence: 99%
“…These rules and standards have been and will continue to be modified, as we learn more about our capacities and acquire more complex technology, as we try to improve our systems for assigning and imposing accountability, and as we struggle to close the considerable gaps in consensus regarding many of the principles 19 20. Still, as we scan our recent past and near future, it is becoming increasingly clear that this framework is crucial in allowing us to understand, criticise, and moderate our actions in war and peace.…”
Section: A Crucial Frameworkmentioning
confidence: 99%